(untitled) (Journal of Educational Sciences, 2023)
This article’s main goal is to organize the concepts of researchers who have studied the issue. In this direction, we focus only on materials indexed in the Scopus database. In this study, «Professional personality» was taken as the main keyword, and to solve the problem, a bibliometric and qualitative content analysis of the materials found in the database was carried out. The author of the article prioritized 41 pieces of scientific literature in order to do content analysis and to fulfill the study’s findings. Priority literature for analysis is written in 5 languages: English (26); Spanish (6); French (4); Russian (4); German (1). To solve research problems, we need answers to two fundamental problems. The results and discussion of the article consist of 2 sections. The first section discusses the prerequisites, goals, and structures of the formation of a professional personality. In this section, we focus on 12 main issues, such as the concept of a professional personality, the stages of becoming a professional personality, the development of a professional personality, models of a professional personality, etc. In the second section of the research work, we argue that the pedagogical approaches formed in the framework of medical education are important for the professional formation of personality. This section discusses the influence of gender on the professional personality, the psychological and psychodynamic characteristics of the professional personality, the study strategy aimed at the professional personality, and the other 7 main issues. Key words: professional personality, higher education, experience, values, upbringing.